Paścimabāṃlāra tīrtha - Sena, Pralaẏa, 1932- (Maḍela Pābaliśiṃ Hāusa, 1979)
On the various heritage, history, and religious importance of the various shrines of West Bengal and Tripura; author's travel impressions.